Brazil's Capital Market : Current Status and Issues for Further Development - Park, Joonkyu (IMF Working Papers; Working Paper, 2012)
Capital market development in Brazil is a key policy issue going forward to foster savings, investment and absorptive capacity in a context of prospects for sizable capital flows in the medium term. During the last decade, Brazil has achieved substantial progress in capital market development. The menu of available financial instruments has been expanded, market infrastructure has been reformed and strengthened, and a diversified investor base has been built. Nonetheless, Brazil's capital markets are still facing a number of challenges including prevalent short-term indexation, investors' risk aversion to long-term fixed rate bonds, still low liquidity in the secondary market, and managing the role of BNDES. A shift to a lower yield curve environment should continue to gradually take place. But further progress will require continued policy effort to assure macro stability and financial sector reforms to promote the development of longer-term private finance.